The Efficacy, Safety, and Cost Benefit of Olanzapine versus Aprepitant in Highly Emetogenic Chemotherapy: A Pilot Study from South India. (27th January 2016) - Babu, Govind; Saldanha, Smitha Carol; Kuntegowdanahalli Chinnagiriyappa, Lakshmaiah; Jacob, Linu Abraham; Mallekavu, Suresh Babu; Dasappa, Loknatha; Kiran, Pretesh Rohan; Sreevatsa, Aparna; Appachu, Sandhya; Unnikrishnan, Vineetha; Arroju, Venugopal
Abstract : Background . The efficacy, safety, and cost benefit of olanzapine (OLN) when compared to aprepitant (APR) in the prevention of chemotherapy induced nausea and vomiting (CINV) in patients receiving highly emetogenic chemotherapy (HEC) were evaluated. Methods . A prospective pilot study was done in chemotherapy-naive patients receiving HEC to compare OLN versus APR along with palonosetron and dexamethasone. 100 patients consented to the protocol and were randomized and evaluated for Complete Response (CR) (no emesis, no rescue). Results . CR was 86% for the acute period, 86% for the delayed period, and 80% for the overall period in 50 patients receiving the APD regimen. CR was 84% for the acute period, 88% for the delayed period, and 78% for the overall period for 50 patients receiving the OPD regimen. Patients without nausea were APD: 88% acute, 84% delayed, and 84% overall, and OPD: 84% acute, 88% delayed, and 84% overall. There were no significant grade 3 or 4 toxicities. OPD was comparable to APD in the control of CINV. Conclusion . In this study, there was no significant difference between olanzapine and aprepitant in preventing CINV with highly emetogenic chemotherapy. Olanzapine may thus be used as a potential, safe, and cost beneficial alternative to prevent nausea and vomiting in HEC.